Tera50+ : sub-mm-wave 100 Gbit/s fiber-wireless transmission system Tera50+ : Sub-mm-Wellen-100-Gbit/s-Glasfaser-Funk-Übertragungssystem - Alissa, Mai; et al. (Wireless 100 Gbps and beyond : architectures, approaches and findings of German Research Foundation (DFG) Priority Programme SPP1655, 2020)
In 2012 a group of researchers proposed a basic research initiative to the German Research Foundation (DFG) as a special priority project (SPP) with the name: Wireless 100 Gbps and beyond. The main goal of this initiative was the investigation of architectures, technologies and methods to go well beyond the state of the art. The target of 100 Gbps was set far away from the (at that time) achievable 1 Gbps such that it was not possible to achieve promising results just by tuning some parameters. We wanted to find breakthrough solutions. When we started the work on the proposal we discussed the challenges to be addressed in order to advancing the wireless communication speed significantly. Having the fundamental Shannon boundary in mind we discussed how to achieve the 100 Gbps speed.
Keywords: Drahtloses Sensorsystem; Hochfrequenztechnik; Antenne; Terahertzbereich; Energieffizienz